Sustainable Polyvinyl Alcohol/Chitosan Biocomposite Films Reinforced With Crystalline Microcellulose Extracted From Waste Notebook Paper - Nguyen, Vu Viet Linh; Phung, Minh Khanh Hao; Nguyen, Thai Hoa; Nguyen, Vinh Tien; Nguyen, Van Quy (Journal of Technical Education Science, 2026)
The micro composite film based on crystalline cellulose and biodegradable polymers has attracted tremendous attention because of its numerous applications in food preservation, medicine, and water purification. This study develops sustainable biocomposite films composed of polyvinyl alcohol (PVA) and chitosan (CS), reinforced with crystalline microcellulose (CMCs) extracted from used notebook paper. After bleaching and acid hydrolysis, CMCs were obtained with a yield of 35.3%, an average size of 615.15 ± 6.7 nm, and the crystallinity index (CrI) of 53.1% was determined by dynamic light scattering (DLS) and X-ray diffraction (XRD), respectively. The extracted CMCs were incorporated into the PVA and CS matrix with different concentrations of 0, 3, and 6 wt.% using a solution casting-evaporating technique to fabricate the PVA/CS@CMC composites. Photographs, SEM images, and transmittance measurements show that the transparency of these biocomposite films decreases when increasing the CMC content. The FTIR spectra indicate that these biocomposite films simultaneously present the characteristic peaks of CMCs and the PVA/CS matrix polymer. In addition, these biocomposite films display a typical crystalline peak of PVA at 2 of 19.76° and two characteristic cellulose I peaks of CMCs at 2 of approximately 14° and 16–17°. Moreover, the composite film with 3 wt.% CMCs exhibits the highest value in the tensile strength. This study suggests that the CMCs derived from used notebook paper can be used as an effective reinforcing material for the PVA/CS blends, offering promising applications in packaging and related fields.